Peningkatan Pengetahuan Kesehatan Gigi dan Mulut melalui Penyuluhan bagi Guru KB-TK Santa Maria Juanda - Stefani, Rosita; Widyastuti, Wiena; Wijaya, Haryanto; Sandra, Ferry; Nadiah, Najla; Suwandi, Trijani; Hadrian, Gary; Victor Reiner Sutanto, Aldrich; William Yusuf, Timotius (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Dental caries is a significant health issue in Indonesia, particularly among preschool children, due to a lack of knowledge and habits in maintaining dental hygiene. Schools serve as strategic venues to promote dental health through activities such as tooth-brushing programs. Teachers play a crucial role in setting examples and guiding children in practicing routine oral hygiene. A health education program at Santa Maria Juanda Kindergarten aims to enhance awareness and understanding of oral health among teachers and students. Based on the pretest and posttest results, this results demonstrate an increase in knowledge by 12.69%, and participants are expected to be able to use the knowledge they have acquired in their everyday lives.